2014
DOI: 10.1039/c3nr04161a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pressure on the post-synthetic modification of a nanoporous metal–organic framework

Abstract: Here we report four post-synthetic modifications, including the first ever example of a high pressure-induced post-synthetic modification, of a porous copper-based metal-organic framework. Ligand exchange with a water ligand at the axial metal site occurs with methanol, acetonitrile, methylamine and ethylamine within a single-crystal and without the need to expose a free metal site prior to modification, resulting in significant changes in the pore size, shape and functionality. Pressure experiments carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…S11 online), showed well resolved peaks of crystalline nature. The results were comparable to simulated pattern and reported literature [6,7,24,28,[39][40][41] which confirmed the successful synthesis of these CMOFNs except DUT-4 and MOF-177.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…S11 online), showed well resolved peaks of crystalline nature. The results were comparable to simulated pattern and reported literature [6,7,24,28,[39][40][41] which confirmed the successful synthesis of these CMOFNs except DUT-4 and MOF-177.…”
Section: Resultssupporting
confidence: 89%
“…Previous reports suggested that nitrogen containing MIL 53(Cr) has an additional binding energy peak at 400 eV, however, here no peaks were observed at $400 eV, corresponding to nitrogen [24], in any of the spectra, which confirmed the absence of 2-MIM in the final product. Only C, O and corresponding metal signals were existed in the spectra [25][26][27][28]. Similar results were obtained using EDS elemental mapping (Fig.…”
Section: Resultssupporting
confidence: 84%
“…27,28 The PSM of MOFs may, in general, be carried out in four different ways: 1) by introducing a new functional group via modification of the organic spacer; [28][29][30][31][32][33][34][35] 2) by anchoring new functionality to the open metal sites in the framework structure; 26,[36][37][38][39][40][41][42] 3) by exchanging the guest species in the cavities of the networks; 43-48 4) by substituting the building blocks of the framework structures, namely, metal ions and/or the organic ligands, with new building blocks via metathesis reaction without disturbing the overall integrity of the framework structure. 27,28 The PSM of MOFs may, in general, be carried out in four different ways: 1) by introducing a new functional group via modification of the organic spacer; [28][29][30][31][32][33][34][35] 2) by anchoring new functionality to the open metal sites in the framework structure; 26,[36][37][38][39][40][41][42] 3) by exchanging the guest species in the cavities of the networks; 43-48 4) by substituting the building blocks of the framework structures, namely, metal ions and/or the organic ligands, with new building blocks via metathesis reaction without disturbing the overall integrity of the framework structure.…”
Section: Introductionmentioning
confidence: 99%
“…DAC experiments in MOFs have become a favourable method for exploring mechanical stability, [4] inducing ligandexchange reactions, [5] locating gas molecules in the pores, [6] causing changes in pore size and guest content, [7] and even inducing low-temperature melting of amorphous frameworks. [8] These breakthroughs have been possible due to the way in which pressure is applied to these systems inside a DAC; crystals of the MOF are placed inside the cavity and surrounded with a liquid (hydrostatic) medium in order to apply pressure evenly to the sample.…”
mentioning
confidence: 99%